2020
DOI: 10.3390/agronomy10010137
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Fluorescence, Photosynthesis and Growth of Tomato Plants as Affected by Long-Term Oxygen Root Zone Deprivation and Grafting

Abstract: A greenhouse experiment was conducted to study the effects of the O2 root zone level and grafting on chlorophyll fluorescence, photosynthesis and growth of cherry tomato grown in a hydroponic system. Two O2 concentrations in the root zone, namely Ox (saturation level) and Ox- (2–3 mg L−1), were applied for 30 days on self-grafted cherry tomato Dreamer or grafted onto the hybrids Arnold, Beaufort, Maxifort and Top Pittam. Root hypoxia increased minimum fluorescence (by 10%) while it decreased variable fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
(44 reference statements)
3
15
0
Order By: Relevance
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in Fv/Fm was noted in more sensitive tomato and cucumber plants in our experiments. In agreement with our results, a decrease in Fv/Fm after waterlogging was also observed in rice [54,57], cucumber [56,58], tomato [59,60], wild tomato (Solanum habrochaites S.Knapp & D.M.Spooner) [61], Arabidopsis (Arabidopsis thaliana L.) [62], cotton [39], and pepper (Capsicum annuum L.) plants [63]. Barik et al [57] examined the reaction of tolerant and susceptible varieties of rice to submergence and observed that the latter exhibited a greater reduction in Fv/Fm parameters in comparison to tolerant varieties.…”
Section: Discussionsupporting
confidence: 93%
“…Each net experimental unit contained 12 plants. During the cycle, the crop was uniformly fertigated with a standard nutrient solution [23], adopting a leaching fraction of at least 75%, to avoid root zone salinization [24]. From 14 to 16 May, tomatoes belonging to the 4th cluster were harvested by hand at the red stage (stage F) according to Gautier et al [25].…”
Section: Growth Conditions Fruit Sampling and Storagementioning
confidence: 99%
“…The results prove the stimulatory effect of foliar auxin application in tomatoes plant growth, the best results being obtained by using HDEEA-pABA and IAA, respectively, at a 0.5 mM concentration. Plants with a large number of leaves show an increased photosynthetic potential, which allows the synthesis, transport, and accumulation of larger amounts of valuable bioactive compounds [57,58].…”
Section: Biological Studiesmentioning
confidence: 99%